Kontribusi Perusahaan Di Sektor Pariwisata Terhadap Produk Domestik Regional Bruto (PDRB) Kota Manado - Stelly S. Morasa; Richard T. Poluan; Astrieth Fenny Patrisia Soputan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Gross Regional Domestic Product (GRDP) illustrates the ability of a region to create output on a certain period. Gross value can be seen from the development and growth of the economy including the tourism sector in certain years in Manado city. The aim of this research was to identify and describe the contributions of the companies in the tourism sector to the GRDP of Manado City. This research was conducted at Manado City Tourism Office, Central Bureau of Statistics Manado City, and in some tourism industries that exist in Manado City, such as hotels, restaurants and travel agents. This research used quantitative methods with statistical mathematical and descriptive approaches using the analysis percentage of GRDP. The results show that the contribution of GRDP of tourism sector to the total GRDP of Manado City have increase. It was found also that the company's biggest contribution in the tourism sector to GRDP were from trade, hotels and restaurants and the smallest was from the entertainment and recreation. The increased in contribution of the tourism industry sector was caused by the construction of new hotels, restaurants, newly built tourism objects and improved existing tourism objects and other support facilities.